Effect of High Hydrostatic Pressure Combined with Natural Inhibitors on Polyphenol Oxidase Activity and Related Quality Attributes of Cloudy Apple Juice - TIAN Xuezhi, CAO Zhihong, JIANG Naixiang, XIAO Zhijian, TANG Zheng, WANG Yongtao (Shipin Kexue)
The effect of high hydrostatic pressure (HHP) treatment combined with either of two natural inhibitors, ferulic acid (FA) or epigallocatechin gallate (EGCG) on polyphenol oxidase (PPO) activity and related quality attributes in cloudy apple juice was explored. The results showed that the addition of 0.1 g/100 mL FA or 0.2 g/100 mL EGCG effectively reduced PPO activity in samples, thereby significantly increasing brightness values (P < 0.05). After HHP treatment (550 MPa/5 min), the relative residual activity of PPO was as high as 82.70%, whereas it decreased to 66.35% and 41.50% after HHP + FA and HHP + EGCG treatment, respectively. During 14 days of refrigeration, PPO activity continued to decrease, while color parameters remained stable. On day 14, the HHP + FA group exhibited the lowest brown index (BI) of 4.37, while the HHP + EGCG group had the lowest relative residual PPO activity of 24.71%. Furthermore, both treatments retained more than 80% of the total phenol content and more than 90% of the antioxidant capacity. In conclusion, combined treatment of HHP with FA or EGCG could effectively inhibit the enzymatic browning of cloudy apple juice, demonstrating potential for further promotion and application.